2001
DOI: 10.1177/14614440122226092
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Introducing Information and Communication Technologies to the Kelabit Community of North Central Borneo

Abstract: This article describes an action-research pilot project to provide opportunities for the remote Kelabit community in the Malaysian state of Sarawak, on the island of Borneo, to use information and communication technologies (ICTs) for sustainable human development. The project aims to establish a telecentre as a place for the community to use ICTs. Although many in the community have heard about computers, they have not seen or used them. In Phase 1 of this project, a team of University Malaysia Sarawak (UNIMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…If CMC technologies are to fulfill their promise for greater equality and what Friere calls critical empowerment -that is, the preservation and enhancement of a community's specific epistemologies and communicative preferences -these technologies must be designed and used in ways that are consistent with the cultural preferences for orally based, collaborative approaches to gaining knowledge. More broadly, the contrast between Western Cartesian and indigenous non-Cartesian epistemologies and learning styles brought to the foreground in these and similar examples (see Harris et al 2001 andSy 2001) again suggests from an empirically grounded viewpoint that the Cartesian epistemology and correlative sense of individual sense is not universal but culturally limited. 12…”
Section: Epistemological Gleaningsmentioning
confidence: 92%
“…If CMC technologies are to fulfill their promise for greater equality and what Friere calls critical empowerment -that is, the preservation and enhancement of a community's specific epistemologies and communicative preferences -these technologies must be designed and used in ways that are consistent with the cultural preferences for orally based, collaborative approaches to gaining knowledge. More broadly, the contrast between Western Cartesian and indigenous non-Cartesian epistemologies and learning styles brought to the foreground in these and similar examples (see Harris et al 2001 andSy 2001) again suggests from an empirically grounded viewpoint that the Cartesian epistemology and correlative sense of individual sense is not universal but culturally limited. 12…”
Section: Epistemological Gleaningsmentioning
confidence: 92%
“…In countries where Internet and computer use is low, the Internet is commonly accessed through cyber cafes (Gigli 2004;Hong and Huang 2005;Mutula and Sairosse 2004;Wahid et al 2006), 'cyber kiosks' (Sreekumar 2007;Yunus 1998) and tele-centres in public places such as libraries, health clinics, community centres and schools (Cole 2000;Harris et al 2001;Rogers and Shukla 2001). Studies have found that young people in developing countries access the Internet mainly for recreational and instrumental purposes such as communicating (chat rooms and e-mails); downloading (computer games, music and software); and obtaining information (about education, entertainment, sports and politics) (Gigli 2004;Hong Huang, 2005;Mutula and Sairosse 2004;Wahid et al, 2006).…”
Section: The Media and Youth In Developing Countriesmentioning
confidence: 98%
“…Other work has focused on quantifying technology uptake and penetration in rural and remote regions (e.g., [19,20,21,35]). Examinations of access to broadband and user uptake in rural North America (in particular the United Sates) include those by Glasmeier et al [19], Wolff et al [35] and Glass and Stefanova [20].…”
Section: Penetration Of Networked Technology In Rural/remote Environmmentioning
confidence: 99%